2015
DOI: 10.1186/s12874-015-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of self-reported toothbrushing frequency as an indicator for the assessment of oral hygiene in epidemiological research on caries in adolescents: a cross-sectional study

Abstract: BackgroundIn the present state of knowledge regarding the etiology of dental caries, it is unacceptable for studies addressing factors associated with this outcome to disregard oral hygiene. Simple, valid methods are needed for the assessment of oral hygiene in adolescents to allow this condition to be properly investigated in epidemiological studies on caries and assist in the establishment of health promotion measures. The aim of the present study was to test the hypothesis that the self-reported toothbrushi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 15 publications
(18 reference statements)
1
25
0
2
Order By: Relevance
“…The HC group participants were motivated and supported to explore and to activate their potential to attain multiple healthy behaviours in their self-management routines, and thus may lead to improvement in periodontal health and glycaemic control; this is in line with earlier studies that showed that taking part in an intervention focusing on empowerment for diabetes self-management had a positive and sustainable impact on the management of health behaviours and glycaemic control 48,49 . Studies have shown that the coaching groups compared with the control groups significantly reduced the body-weight and fat and coronary heart disease factors including BMI 50,51 . In line with these studies, the Turkish HC group significantly reduced body fat percentage and improved the lean mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HC group participants were motivated and supported to explore and to activate their potential to attain multiple healthy behaviours in their self-management routines, and thus may lead to improvement in periodontal health and glycaemic control; this is in line with earlier studies that showed that taking part in an intervention focusing on empowerment for diabetes self-management had a positive and sustainable impact on the management of health behaviours and glycaemic control 48,49 . Studies have shown that the coaching groups compared with the control groups significantly reduced the body-weight and fat and coronary heart disease factors including BMI 50,51 . In line with these studies, the Turkish HC group significantly reduced body fat percentage and improved the lean mass.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of the prevalence of health behaviours as part of research is vitally important and often requires the use of self-report measures. There is an inherent error risk in self-reported measures, however, if this error were constant over time, it could still be used as a good comparison criterion among epidemiological studies 16,51 . The present study could have minimised this limitation; self-reported measures were assessed over time and also analysed along with clinical measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, periodontal status was assessed as pocket depth, which T A B L E 2 Brushing twice a day or more often at baseline (2000) and follow-up (2011), by baseline characteristics (n = 1,025) Third, information on toothbrushing behaviour was collected through self-reports. Although some might argue that dental plaque indices provide a stronger assessment of oral cleanliness, there is evidence of good correlation between self-reported toothbrushing frequency and oral hygiene indices (Gil et al, 2015;Harnacke et al, 2015). More importantly, current recommendations on plaque control and oral hygiene maintenance are based on habitual toothbrushing behaviour, not clinical levels of dental plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions aimed at controlling plaque and improving oral health often have only a shortterm effect. Flossing after brushing and not before, and a positive attitude promote better oral hygiene habits [3][4][5][6][7][8][9][10][11][12][13][14][15] .…”
mentioning
confidence: 99%